Leadership in the reform of Malaysian universities: analysing the strategic role of the Malaysian Qualifications Agency - Ahmad Bajunid, Ibrahim (Taylor Francis Group, 2011)
This paper addresses the contemporary development and reform challenges in tertiary education in Malaysia in both national and global contexts. The critical role exercised by the Malaysian Qualifications Agency in driving strategic change in higher education cultures, both in public and private universities is described and analysed. The paper examines the adoption, generation and institutionalisation of global standards of prac- tice in teaching and learning and in other fundamental dimensions of the provision of quality education. Contending ideas, rationales and models of universities and the con- tributions this institution makes to educational provisions are examined. The analyses are informed by the development reforms in other sectors of government and society within the integrated framework of the nation’s strategic vision of development – Vision 2020.